2005
DOI: 10.1073/pnas.0504068102
|View full text |Cite
|
Sign up to set email alerts
|

Highways of gene sharing in prokaryotes

Abstract: The extent to which lateral genetic transfer has shaped microbial genomes has major implications for the emergence of community structures. We have performed a rigorous phylogenetic analysis of >220,000 proteins from genomes of 144 prokaryotes to determine the contribution of gene sharing to current prokaryotic diversity, and to identify ''highways'' of sharing between lineages. The inferred relationships suggest a pattern of inheritance that is largely vertical, but with notable exceptions among closely relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
511
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(544 citation statements)
references
References 35 publications
28
511
2
3
Order By: Relevance
“…Extensive HGT among thermophiles, pathogens and cyanobacteria has been described previously, for example, 'highways' of HGT (Doolittle, 1998;Beiko et al, 2005), and was attributed to substantial ecological overlap among the partners involved. Along the same lines, a recent study of intra-phylum HGT showed that very recent gene transfer events (reflected by 499% nucleotide sequence identity) are clearly structured by ecology, where the highest frequency of HGT was observed among organisms recovered from the same site of the human body (Smillie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive HGT among thermophiles, pathogens and cyanobacteria has been described previously, for example, 'highways' of HGT (Doolittle, 1998;Beiko et al, 2005), and was attributed to substantial ecological overlap among the partners involved. Along the same lines, a recent study of intra-phylum HGT showed that very recent gene transfer events (reflected by 499% nucleotide sequence identity) are clearly structured by ecology, where the highest frequency of HGT was observed among organisms recovered from the same site of the human body (Smillie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent analysis of protein families suggests that HGT, and not gene duplication, has driven protein expansion and functional novelty in bacteria, which is in contrast with most eukaryotic organisms (Treangen and Rocha, 2011). Sequencing of thousands of microbial genomes during the past two decades has allowed the identification of HGT events at different timescales, from ancestral to recent events, and between organisms of varied evolutionary relatedness, from closely related genomes to very distantly related ones (Gogarten et al, 2002;Beiko et al, 2005;Ochman et al, 2005;Zhaxybayeva et al, 2009a), revealing that HGT has affected the evolutionary history of most, if not all, bacterial lineages.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,11,12 . Such patterns are probably a consequence of existing barriers to HGT, which have been reviewed in detail elsewhere 13,14 .…”
Section: Competing Interests Statementmentioning
confidence: 99%
“…An extreme case is genome chimerism, as discussed previously. As far as bacteria are concerned, neither Beiko et al (2005) nor Ge et al (2005) detected strong evidence for preferential genetic exchanges between specific phyla: according to these studies, bacterial gene trees are more or less randomly distributed around the species tree (but see Matte-Taillez et al 2002;Jain et al 2003). We note that there is a convergence between practical and conceptual aspects here; the task of reconstructing 'the' species tree is more and more difficult, and more and more pointless, as the distribution of true gene trees becomes multimodal.…”
Section: Can We Still Recover the Species Tree?mentioning
confidence: 99%